2013
DOI: 10.1634/theoncologist.2013-0239
|View full text |Cite
|
Sign up to set email alerts
|

New Oral Anticoagulants and the Cancer Patient

Abstract: Learning Objectives Cite the current indications, basic clinical pharmacology, and rationale for development of the new oral anticoagulants. Explain the potential risk for drug‐drug interactions between the new oral anticoagulants and drugs commonly used in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
1
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(174 citation statements)
references
References 69 publications
0
153
1
20
Order By: Relevance
“…A fourth factor Xa inhibitor, betrixaban, is undergoing phase 3 trials. 56,57 The DOACs are target specifi c and bind coagulation factor catalytic sites in a dose-dependent manner, which results in a rapid onset of activity (<4 h) that precludes the need for parenteral anticoagulation. LMWH inhibits factor Xa indirectly by activating and accelerating antithrombin action.…”
Section: Early Maintenance (10 Days To 3 Months) and Long-term (Beyonmentioning
confidence: 99%
“…A fourth factor Xa inhibitor, betrixaban, is undergoing phase 3 trials. 56,57 The DOACs are target specifi c and bind coagulation factor catalytic sites in a dose-dependent manner, which results in a rapid onset of activity (<4 h) that precludes the need for parenteral anticoagulation. LMWH inhibits factor Xa indirectly by activating and accelerating antithrombin action.…”
Section: Early Maintenance (10 Days To 3 Months) and Long-term (Beyonmentioning
confidence: 99%
“…The challenge may be to consider explanations for findings that may not be obvious at first glance, but nonetheless signal unprecedented opportunities for progress in cancer prevention and treatment. New peptide anticoagulants with specificity for the active serine site of factor Xa and thrombin should gain access readily to the extravascular environment of cancer (51) needed for inhibition of tumor progression (52). Clinical trials may be indicated in tumor types, such as malignant melanoma (6,7,(53)(54)(55)(56) and renal cell carcinoma (6,7,57), having tumor cell induced coagulation activation similar to that of SCCL.…”
Section: Discussionmentioning
confidence: 99%
“…Практическое значе-ние исследования весьма ограничено, так как пока-занием к применению бозутиниба является только хро-нический миелолейкоз, положительный по фила-дельфийской хромосоме, причем лишь в случае не-переносимости или неэффективности предшествую-щей терапии хотя бы одним из ингибиторов тиро-зинкиназ, включая иматиниб, дазатиниб и/или ни-лотиниб [43]. Взаимодействие НОАК с более широко применяемыми таргетными препаратами, многие из которых ингибируют CYP3A4 и/или P-gp (например, те же иматиниб, дазатиниб, нилотиниб [44]), остает-ся неизученным.…”
Section: Drug Interactions Of Noac лекарственные взаимодействия ноакunclassified